Electroacupuncture Upregulates HIF-1α and SOX9 Expression in Knee Osteoarthritis - Jie Tong (Hindawi Limited, 2021)
Electroacupuncture (EA) has been clinically used in knee osteoarthritis broadly and proved to be effective than other therapies with fewer side effects; however, the mechanism of electroacupuncture to work on cartilage remains unclear. In this study, we aimed to evaluate the effect of EA treatment on cartilage and the relationship between EA and proteins such as HIF-a and SOX9. EA (dilatational wave, 3–15 HZ, 1 mA) has been applied to bilateral Zusanli (ST36), Xuehai (SP10), Taixi (KI3), and Yanglingquan (GB34) of rats. Results showed that the cartilage of the knee osteoarthritis group had obvious damage and fissure formation while the EA group showed that the cartilage destruction was generally milder. In addition, the protein expression levels of HIF-1α, and chondrogenic markers such as Sox9, and ACAN in the electroacupuncture group were higher than those in the ACLT group. Also, the extracellular matrix protein expression levels of MMP13 and ADAMTS5 were decreased in the EA group. These findings indicate that EA could alleviate the severity of knee osteoarthritis, and HIF-a and SOX9 may closely attribute to the treatment.